2018
DOI: 10.1038/s41413-018-0009-8
|View full text |Cite
|
Sign up to set email alerts
|

Super enhancer inhibitors suppress MYC driven transcriptional amplification and tumor progression in osteosarcoma

Abstract: Osteosarcoma is the most common primary bone sarcoma that mostly occurs in young adults. The causes of osteosarcoma are heterogeneous and still not fully understood. Identification of novel, important oncogenic factors in osteosarcoma and development of better, effective therapeutic approaches are in urgent need for better treatment of osteosarcoma patients. In this study, we uncovered that the oncogene MYC is significantly upregulated in metastastic osteosarcoma samples. In addition, high MYC expression is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 35 publications
(52 reference statements)
4
106
0
Order By: Relevance
“…In recent years, developments in molecular biology have provided new insights into potential diagnostic and therapeutic biomarkers for osteosarcoma. Previous study demonstrated that prometastasis genes such as MYC and RAS facilitate osteosarcoma metastasis and metastasis‐resistant genes including nm23 , p16 and KiSS‐1 metastasis‐suppressor inhibited the metastasis process in osteosarcoma. Furthermore, microarray technology has been widely used for screening a series of metastasis‐related genes in osteosarcoma .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, developments in molecular biology have provided new insights into potential diagnostic and therapeutic biomarkers for osteosarcoma. Previous study demonstrated that prometastasis genes such as MYC and RAS facilitate osteosarcoma metastasis and metastasis‐resistant genes including nm23 , p16 and KiSS‐1 metastasis‐suppressor inhibited the metastasis process in osteosarcoma. Furthermore, microarray technology has been widely used for screening a series of metastasis‐related genes in osteosarcoma .…”
mentioning
confidence: 99%
“…In recent years, developments in molecular biology have provided new insights into potential diagnostic and therapeutic biomarkers for osteosarcoma. Previous study demonstrated that prometastasis genes such as MYC [7,8] and RAS [9] facilitate osteosarcoma metastasis and metastasis-resistant genes including nm23 [10], p16 [11] and KiSS-1 metastasis-suppressor [12] inhibited the metastasis process in osteosarcoma.Abbreviations AUC, area under receiver operating characteristic curve; GEO, Gene Expression Omnibus; GO, gene ontology; KEGG, Kyoto Encyclopedia of Genes and Genomes; LASSO, least absolute shrinkage and selection operator; ROC, receiver operating characteristic.…”
mentioning
confidence: 99%
“…Univariate Cox regression and Lasso Cox regression analysis showed that a gene signature composed of 9 autophagy-related genes (BNIP3, MYC, BAG1, CALCOCO2, ATF4, AMBRA1, EGFR, MAPK1, and PEX3) was closely related to the prognosis of OS. Studies have shown that the abnormal expression of MYC [52], ATF4 [53], and MAPK1 [54] is related to the proliferation, migration, and invasion of OS cells. As a transcription target of MYC, BAG1 cooperates with HSP70 molecular chaperone to selectively mediate MYC overexpression and affect the survival of OS cells [55].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identification of new specific metastasis‐associated molecules as therapeutic targets or independent predictors of OS metastasis is needed. Recently, many potential prognostic biomarkers and therapeutic targets have been discovered, including MYC and RAS were reported to facilitate OS metastasis. Previous studies found that some genes, such as p16 and nm23 could also inhibit the metastatic process in OS.…”
Section: Introductionmentioning
confidence: 99%